2015
DOI: 10.1186/s12955-015-0341-2
|View full text |Cite
|
Sign up to set email alerts
|

Mental distress among Liberian medical staff working at the China Ebola Treatment Unit: a cross sectional study

Abstract: BackgroundEbola virus outbreak in West Africa not only triggered a grave public health crisis, but also exerted and induced huge mental distress on medical staff, which would negatively influence epidemic control and social rebuilt furthermore. We chose the local medical staff working at the China Ebola Treatment Unit (ETU) to explore the severity of potential mental distress and involved potential causes.MethodsA descriptive study using the Symptom Check List 90 - Revised (SCL90-R) questionnaire to assess psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
114
6
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(125 citation statements)
references
References 27 publications
3
114
6
2
Order By: Relevance
“…Generally, unmet medical need occurrence was higher for military personnel who had no time to go for medical service and experienced difficulty in making an appointment or long office waits. This finding corroborates those from previous studies that determined that military personnel often experience decreased QOL and eventual mental health-related hospitalisation as a result of unmet medical need 25. In addition, depressive symptoms typically predict greater medical care utilisation,26 although suicide ideation could be reduced by healthcare intervention 27…”
Section: Discussionsupporting
confidence: 87%
“…Generally, unmet medical need occurrence was higher for military personnel who had no time to go for medical service and experienced difficulty in making an appointment or long office waits. This finding corroborates those from previous studies that determined that military personnel often experience decreased QOL and eventual mental health-related hospitalisation as a result of unmet medical need 25. In addition, depressive symptoms typically predict greater medical care utilisation,26 although suicide ideation could be reduced by healthcare intervention 27…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, HCWs in West African ETCs had high rates of mental distress during the outbreak [35]. In contrast, a study on mental distress among Liberian medical staff working at the Chinese ETC found that mental distress among study participants was not as serious [22]. This study found two distinctive health protection strategies were employed to ensure the health of the CMMT.…”
Section: Discussionmentioning
confidence: 73%
“…Although studies have previously reported on various mental health [22] and physical measures taken by Chinese ETCs to protect HCWs from EVD infection [23,24], these studies were all conducted in China, and only reported on measures taken during the mission, and did not report on measures taken before and after the mission. No study has yet analysed the full spectrum of bio-psycho-social risk factors to which HCWs are exposed throughout their mission.…”
Section: Introductionmentioning
confidence: 99%
“…Despite our broad search, we only identified one study from a low to middle income country. 20 In addition, we were unable to locate the full text of nine studies that might have been relevant. Only three studies Increased contact with affected patients 6 14 16-18 23 25 26 31 33 36 38 39 41 44 47-49 53 55 56 58-60 62-64 66 67 70 ○ Precautionary measures creating perceived impediment to doing job 50 64 ○ Forced redeployment to look after affected patients 35 55 ○ Higher risk among nurses* 6 23 30 41 50 55 57 64-66 • Training and experience ○ Inadequate training 6 42 ○ Lower levels of education 46 ○ Part time employee 50 ○ Less clinical experience 6 18 36 42 • Personal ○ Increased time in quarantine 14 33 38 59 63 70 ○ Staff with children at home 41 66 ○ Personal lifestyle impacted by epidemic/pandemic 50 ○ Infected family member 25 29 59 ○ Single or social isolation 34 66 70 ○ Female sex † 6 16 23 26 29 36 ○ Lower household income 59 63 ○ Comorbid physical health conditions 29 40 55 67 ○ Younger age ‡ 32 50 55 59 69 • Psychological ○ Lower perceived personal self-efficacy 40 42 ○ History of psychological distress, mental health disorders, or substance misuse 29 42 45 46 48 53 54 66 69 Service factors • Perceived lack of organisational support 12 38 47 48 55 66 • Perceived lack of adequacy of training 48 • Lack of confidence in infection control 37 • No compensation for staff by organisation 13 43 Societal factors • Societal stigma against hospital workers 15 40 41 50 51 66 All studies cited in box are high quality apart from references 13,14,26,30,[39][40][41]54, and 52.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%